Pengembangan Modul Praktikum Kimia Berbasis Problembased Learning (PBL) Pada Materi Larutan Elektrolit Dannonelektrolit Dengan Model ADDIE - Robialdus Jehadut; Maria Benedikta Tukan; Faderina Komisia (Journal on Education, 2024)
This development research is motivated by a problem where teaching materials or practicum modules for all learning materials are not yet available. For this reason, it is necessary to integrate practicum modules with problem-based learning models in one of the learning materials, namely, material for electrolyte and non-electrolyte solutions. The aims of this study were (1) to find out the validity of the problem-based learning chemistry practicum module on electrolyte and non-electrolyte solution material, (2) to find out students' responses to problem-based learning chemistry practicum modules on electrolyte and non-electrolyte solution material. The research design used is the ADDIE model which is limited to 3 stages, namely Analysis, Design, Development. The results of this study are (1) the validity of the practicum module obtained from the assessment of 2 validators, namely material experts in the very feasible category and the media expert validator in the very feasible category, (2) The results of students' responses to the problem-based learning chemistry practicum module belong to the category both with a percentage of 77.47%.